Regresión lineal con errores no normales: secante hiperbólica generalizada (2014)
This paper presents a study of the model of linear regression of the type y = Θx + e, where the error has generalized hyperbolic secant distribution (GHS) -- The method to estimate the parameters are obtained by setting maximum likelihood expressing the non-linear equations in linear form (modified likelihood) -- The resulting estimators are analytical expressions in terms of values of the sample and, therefore, are easily calculables -- Through the application of various types of data, the methodology described above is shown, and plausible models against the true underlying distributions of data are